Robber flies of South Korea III. South Korean species of the Subfamily Laphriinae Macquart, 1838 (Diptera: Asilidae) - Young, Charles L.; Hradský, Milan M. (Zootaxa, 2007)
Three genera and 13 species of the subfamily Laphriinae are recorded from South Korea. New records include: Chorades amurensis (Hermann), C. caucasicus Richter & Mamaev , C. caudatus Lehr , C. komurai (Matsumura), C. nigrovittatus (Matsumura), Choerades sp., Laphria hakiensis Matsumura, and Orthogonis sp. Choerades asprospilos sp. nov. is described. The genus Orthogonis Hermann is a new record for the area. Drawings of diagnostic features, a checklist, keys and descriptions are included. All mentioned species are re-described based on specimens for this study.